Chlamydomonas as a model system to study cilia and flagella using genetics, biochemistry, and microscopy - Marshall, Wallace F. (Frontiers in Cell and Developmental Biology, 2024)
The unicellular green alga, Chlamydomonas reinhardtii, has played a central role in discovering much of what is currently known about the composition, assembly, and function of cilia and flagella. Chlamydomonas combines excellent genetics, such as the ability to grow cells as haploids or diploids and to perform tetrad analysis, with an unparalleled ability to detach and isolate flagella in a single step without cell lysis. The combination of genetics and biochemistry that is possible in Chlamydomonas has allowed many of the key components of the cilium to be identified by looking for proteins that are missing in a defined mutant. Few if any other model organisms allow such a seamless combination of genetic and biochemical approaches. Other major advantages of Chlamydomonas compared to other systems include the ability to induce flagella to regenerate in a highly synchronous manner, allowing the kinetics of flagellar growth to be measured, and the ability of Chlamydomonas flagella to adhere to glass coverslips allowing Intraflagellar Transport to be easily imaged inside the flagella of living cells, with quantitative precision and single-molecule resolution. These advantages continue to work in favor of Chlamydomonas as a model system going forward, and are now augmented by extensive genomic resources, a knockout strain collection, and efficient CRISPR gene editing. While Chlamydomonas has obvious limitations for studying ciliary functions related to animal development or organ physiology, when it comes to studying the fundamental biology of cilia and flagella, Chlamydomonas is simply unmatched in terms of speed, efficiency, cost, and the variety of approaches that can be brought to bear on a question.